Auditoría de gestión a la Empresa Icoplast, ciudad Riobamba, período 2021. - Olivo Olivo, Junior Alexander (2023)
The present research work was developed with the purpose of evaluating the different processes that are desalinated and followed in the company Icoplast, in order to evaluate and analyze them and determine the feasibility and viability of the same. This by means of the elaboration of a management audit, which allows us to know the level of efficiency, efficacy and economy with which the company's resources are used. The period evaluated corresponds to the year 2021, a year in which the objectives and goals set did not achieve, due to a series of lags caused by the uncertainty of the processes with which the company operates, resulting in a series of problems that must be solved immediately in order to do not fall back into the same shortcoming Finally, after having evaluated the management and use of resources, it was possible to determine indicators that focus on the level of process compliance. The level of efficiency, effectiveness and economy of the company was known. And finally the respective final audit report was issued based on the findings detected, where recommendations to be implemented by the company Icoplast raised.